Human apolipoprotein E glycosylation and sialylation: from structure to function - Moon, Hee-Jung; Luo, Yan; Chugh, Diksha; Zhao, Liqin (Frontiers in Molecular Neuroscience, 2024)
Human apolipoprotein E (ApoE) was first identified as a polymorphic gene in the 1970s; however, the genetic association of ApoE genotypes with late-onset sporadic Alzheimer’s disease (sAD) was only discovered 20 years later. Since then, intensive research has been undertaken to understand the molecular effects of ApoE in the development of sAD. Despite three decades’ worth of effort and over 10,000 papers published, the greatest mystery in the ApoE field remains: human ApoE isoforms differ by only one or two amino acid residues; what is responsible for their significantly distinct roles in the etiology of sAD, with ApoE4 conferring the greatest genetic risk for sAD whereas ApoE2 providing exceptional neuroprotection against sAD. Emerging research starts to point to a novel and compelling hypothesis that the sialoglycans posttranslationally appended to human ApoE may serve as a critical structural modifier that alters the biology of ApoE, leading to the opposing impacts of ApoE isoforms on sAD and likely in the peripheral systems as well. ApoE has been shown to be posttranslationally glycosylated in a species-, tissue-, and cell-specific manner. Human ApoE, particularly in brain tissue and cerebrospinal fluid (CSF), is highly glycosylated, and the glycan chains are exclusively attached via an O-linkage to serine or threonine residues. Moreover, studies have indicated that human ApoE glycans undergo sialic acid modification or sialylation, a structural alteration found to be more prominent in ApoE derived from the brain and CSF than plasma. However, whether the sialylation modification of human ApoE has a biological role is largely unexplored. Our group recently first reported that the three major isoforms of human ApoE in the brain undergo varying degrees of sialylation, with ApoE2 exhibiting the most abundant sialic acid modification, whereas ApoE4 is the least sialylated. Our findings further indicate that the sialic acid moiety on human ApoE glycans may serve as a critical modulator of the interaction of ApoE with amyloid β (Aβ) and downstream Aβ pathogenesis, a prominent pathologic feature in AD. In this review, we seek to provide a comprehensive summary of this exciting and rapidly evolving area of ApoE research, including the current state of knowledge and opportunities for future exploration.